Research progress on the mechanism of transcutaneous electrical acupoint stimulation in the perioperative period - Jiang, Xiaobo; Li, Mengqi; Tang, Yuanjian; Hu, Jing; Gai, Xiangmu; Zhang, Chenfeng; Li, Tie; Wang, Yanxin; Wang, Hongfeng (Frontiers in Neurology, 2025)
Transcutaneous Electrical Acupoint Stimulation (TEAS) is a non-invasive therapeutic approach that combines modern electrophysiological technology with traditional Chinese medicine principles. Over the past few decades, TEAS has become a significant medical intervention during the perioperative period and its mechanisms have seen a continuous development. These mechanisms span across multiple aspects, including the regulation of the neuroendocrine network system, inhibition of oxidative stress, alleviation of immune suppression, regulation of endothelial function, and inhibition of coagulation and fibrinolysis system activation. This article aims to summarize and elaborate the mechanisms of TEAS in the perioperative period and to discuss current research challenges. Future studies should strive to optimize treatment protocols to promote the research on the mechanisms of TEAS in the perioperative period, subsequently offering patients safer and more effective treatment alternatives.